Suvorexant for insomnia in patients with psychiatric disorder: A 1‐week, open‐label study - Taro Kishi; Kenji Sakuma; Makoto Okuya; Kohei Ninomiya; Kazuto Oya; Momoko Kubo; Yuki Matsui; Ikuo Nomura; Yuji Okuyama; Shinji Matsunaga; Nakao Iwata (Neuropsychopharmacology Reports, 2019)
Abstract Aim There have been no previous reports on the efficacy and safety of suvorexant for insomnia in people with psychiatric disorders. Methods This one‐week, prospective, single‐arm, clinical trial of fixed dose of suvorexant (20 mg if ages 18–64 or 15 mg if age ≥ 65 years) for insomnia included 57 patients with psychiatric disorders who had experienced any of the following insomnia symptoms for four or more nights during the week prior to the start of the study: total sleep time (TST) <6 hours, time to sleep onset (TSO) ≥30 minutes, or two or more episodes of wake after sleep onset. Results The mean age of the patients was 49.4 ± 17.3 years; 54.4% were women, 49.1% had a major depressive disorder, and 77.2% completed the trial. Compared with the baseline scores (the mean scores for the two days before the start of the study), taking suvorexant was associated with significant improvements in TST, TSO, wake time after sleep onset, and the patients' sleep satisfaction level at week 1. Adverse events included at least one adverse event (43.9%), sleepiness (28.8%), fatigue (11.5%), nightmares (5.8%), headache (3.8%), dizziness (3.8%), and vomiting (1.9%). Conclusion Suvorexant was beneficial for the treatment of insomnia in people with psychiatric disorders. However, this study was of short duration and included only a relatively small number of patients. A larger, long‐term study is needed to investigate the efficacy and safety of suvorexant for insomnia in people with psychiatric disorders.